Evaluating the association between gestational diabetes and neonatal hypoglycemia in Taiwan: a retrospective study of 2,149 pregnancies - Chang, Shiang-Hua; Hsin, Pei-Hsiu; Lin, Jia-Juen; Yang, Yi-Sun; Lo, Shih-Chang; Huang, Chien-Ning; Wang, Yu-Hsun; Kornelius, Edy (Frontiers in Endocrinology, 2025)
ObjectiveTo determine whether gestational diabetes mellitus (GDM) is associated with an increased risk of neonatal hypoglycemia and adverse neonatal outcomes in a Taiwanese population.MethodsWe performed a retrospective cohort study of 2,149 women who delivered at Chung Shan Medical University Hospital from 2019 to 2023. GDM was diagnosed by one-step 75-g oral glucose tolerance test (OGTT). Neonatal hypoglycemia was defined as blood glucose <45 mg/dL. Logistic regression was used to estimate odds ratios (ORs) for neonatal outcomes associated with GDM, adjusting for maternal age, body mass index (BMI), and parity. Other neonatal outcomes included preterm birth, low Apgar scores (≤7 at 1 or 5 minutes), neonatal intensive care unit (NICU) admission, or neonatal jaundice.ResultsOf 2,149 pregnancies, 591 (27.5%) were diagnosed with GDM. Neonatal hypoglycemia occurred in 176 newborns (8.2%). The incidence of hypoglycemia was slightly lower in infants of GDM mothers (6.8%) compared to those of non-GDM mothers (8.7%), but this difference was not statistically significant (adjusted OR 0.70, 95% CI 0.48–1.02). GDM was also not significantly associated with other neonatal outcomes, including preterm birth, low Apgar scores, NICU admission, or neonatal jaundice, after adjusting for confounders.ConclusionsIn this Taiwanese cohort with universal GDM screening and management, GDM was not linked to a higher risk of neonatal hypoglycemia or other immediate neonatal complications. These findings suggest that effective prenatal care and glycemic control may mitigate the neonatal risks traditionally associated with GDM, underscoring the importance of management and population-specific factors in outcomes.